Digital Financial Development and Corporate Technological Innovation: Promotion or Inhibition? - Liu, Dayong; Song, Di; Zhang, Lingxiao; Wang, Yanan (Transformations In Business & Economics, 2024)
Digital finance not only drives the rebuilding of the traditional financing system but also considerably influences microscopic corporate technological innovation and even high-quality economic development. To explore the effects of digital financial development on corporate technological innovation, using panel data of A-share companies on Shanghai and Shenzhen Stock Exchanges in China from 2011 to 2019, and time-industry fixed effect models, according to resource allocation theory and information asymmetry theory, whether digital financial development can facilitate improvements of corporate technological innovation was examined. Results show that: (1) Digital financial development can significantly promote corporate technological innovation. (2) Continuously deepening development of digital finance promotes technological innovation of non-state-owned corporates more clearly than that of state-owned corporates. (3) Digital finance can inhibit financing constraints and financial investment of corporates and plays an important mediating effect on the improvement of corporate technological innovation. (4) According to interaction processing, digital financial development can better drive the improvement of corporate technological innovation in regions with low economic development levels. The conclusions disclose that digital financial development not only promotes corporate technological innovation but also further facilitates high-quality economic progress, which can provide the government with powerful evidence to formulate relevant economic development policies.